Kegagalan Sistem Pemidanaan dalam Memberi Efek Jera bagi Pelaku Eksploitasi Pekerja Migran - Jody Imam Rafsanjani; Zaihan Harmaen Anggayudha (Fakultas Hukum Universitas Islam Indonesia, 2025)
The exploitation of Indonesian migrant workers (PMI) continues despite the enforcement of national regulations such as Law No. 21 of 2007 on the Eradication of Human Trafficking and Law No. 18 of 2017 on the Protection of Migrant Workers. The research question addressed is: why does the Indonesian penal system fail to deter the exploitation of migrant workers? This study employs a normative legal method, using statutory and case study approaches, particularly analyzing court decisions and human rights institution reports. The findings reveal that the ineffectiveness of criminal sanctions, weak implementation of restitution, and a dominant administrative approach in resolving exploitation cases are the main causes of the failure to achieve the objectives of punishment. Therefore, a reformulation of the penal approach is necessary, including harsher sentencing, an expansion of corporate criminal liability, and the integration of restorative justice principles to ensure real protection for migrant workers.